Investigation of differential Multi-Mode antibacterial mechanisms of essential oils of Satureja montana L. and Leptospermum scoparium J.R.Forst. & G.Forst. Against Porphyromonas gingivalis - Yue Yuan; Xiuli Hui; Zixuan Liu; Jinlong Sun; Rifat Nowshin Raka; Junsong Xiao; Zhongwei Zhang; Hua Wu (BMC Complementary Medicine and Therapies)
Abstract Background Globally, according to WHO estimates, severe periodontitis affects over 1 billion people. Porphyromonas gingivalis (P. gingivalis) is a keystone pathogen in the development of chronic periodontitis. Although two commercial essential oils (EOs) derived from Satureja montana L. (EO1) and Leptospermum scoparium J.R.Forst. & G.Forst. (EO2) have demonstrated promising antibacterial potential, their mechanisms against P. gingivalis and the influence of their distinct metabolite profiles remain unclear. Methods EO metabolite profiles were analyzed using gas chromatography-mass spectrometry. Antibacterial activity was assessed using the disk diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and bacterial growth curves. Their effects on hemagglutination, hemolytic, black pigmentation formation, autoaggregation, hydrophobicity, biofilm formation and virulence gene expression were evaluated. Molecular docking simulated interactions between metabolites and the virulence proteins. Cytotoxicity at MIC was tested in RAW264.7 cells using MTT assays. Results EO1 showed stronger antibacterial effects than EO2, with inhibition zone diameters (42.06 ± 1.62 versus 40.36 ± 0.47 mm), lower MIC (71.33 versus 305.00 µg/mL), and MBC (142.66 µg/mL versus 1220.00 µg/mL). The bacterial growth curves demonstrated sustained inhibition. EO1 can inhibit P. gingivalis hemagglutination, hemolysis (p < 0.05), and heme accumulation at 1/8 − 1/2 MIC, while EO2 only affected heme accumulation. Both EOs reduced P. gingivalis hydrophobicity levels below 50% at 1/4 to 1/2 MIC and achieved biofilm inhibition rates exceeding 85% at MIC (p < 0.05). The distinct inhibitory mechanisms against the pathogenic processes of P. gingivalis likely stem from their differing metabolite profiles. EO1 was dominated by monoterpenes (56.00 ± 0.55%), and the main metabolites were γ-terpinene (20.20 ± 0.38%), p-cymene (16.01 ± 0.66%), and carvacrol (14.50 ± 0.35%), whereas EO2 contained up to 71.19 ± 0.18% sesquiterpenes, its main metabolites were leptospermone (17.44 ± 0.40%). Molecular docking analysis predicted these metabolites as key active components. Besides, at MIC, cell viability was 86.68% for EO1 and 68.81% for EO2. Conclusion The comprehensive analysis reveals that EO1 and EO2 exert multi-mode antibacterial effects through different mechanisms. Notably, EO1 demonstrated greater potential against P. gingivalis, which may be attributed to its unique metabolite composition. These findings offer a theoretical foundation and new insights for advancing the application of EOs in the prevention and adjunctive management of periodontitis.